(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the stylistic variations in fairy tales across different cultures, using Hans Christian Andersen’s fairy tales as a primary example. It examines how Andersen’s works stand out due to their blend of realism, emotional depth, and lyrical quality, diverging from traditional fairy tale conventions by incorporating elements of everyday life and moral ambiguity. The article also compares Andersen’s style with those of other cultural traditions, such as German fairy tales by the Brothers Grimm, Japanese folklore, Arabian tales from One Thousand and One Nights, and African oral storytelling. By highlighting these differences, the article underscores the universal themes of fairy tales—such as good versus evil, transformation, and moral lessons—while showing how each culture’s unique stylistic approach reflects its values, traditions, and worldview. The analysis concludes by emphasizing the enduring relevance and global appeal of fairy tales, noting that their stylistic diversity enriches their ability to convey shared human experiences.